Determinants of the length of stay in intensive care and in hospital after coronary artery surgery. Issue 1 (January 1995) - Mounsey, J. P.; Griffith, M. J.; Heaviside, D. W.; Brown, A. H.; Reid, D. S.
Abstract : BACKGROUND--Patients who have coronary artery surgery normally occupy intensive care beds for less than 24 hours. Longer stays may result in under use of cardiac surgical capacity. One approach to optimise surgical throughput is prospectively to identify fast track patients--that is, those who occupy an intensive care bed for less than 24 hours. A prospective audit of patients was performed to identify fast track patients by simple clinical criteria. Total length of hospital stay was also assessed in an attempt to predict which patients were likely to have a short postoperative stay, defined as < or = 7 days. METHODS--Baseline demographic details, cardiovascular risk factors, angiographic and operative details were recorded for 431 consecutive patients who underwent coronary surgery at a regional centre over a nine month period. Outcome measures were the duration of the stay in the intensive care unit in hours and total duration of the postoperative stay in hospital in days. In addition, two groups of patients who were thought to be fast track were identified prospectively. Fast track 1 patients were identified by criteria selected by cardiovascular physicians. These were age less than 60 years, stable angina, good left ventricular function (ejection fraction > 50%), good renal function (serum creatinine < 120 mumol/l), and no obesity, diabetes, or other serious disease. Fast track 2 patients were identified by criteria defined by cardiovascular surgeons. These were male sex, age less than 65 years, good left ventricular function and no peripheral vascular disease, diabetes, or other serious disease. The efficacy of both sets of criteria in predicting outcome was tested. RESULTS--344 (79.8%) patients were fast track. Significant factors for the prediction of fast track patients by univariate analysis (with positive predictive accuracy and sensitivity) were left ventricular ejection fraction > 50% (83%, 80%), left ventricular end diastolic pressure < 13 mm Hg (90%, 59%), creatinine less than 120 mumol/l (83%, 87%), and one or two vessel coronary disease (89%, 34%). Of the patients categorised as fast track 1 89% proved to be fast track (sensitivity 24%), however, the fast track 2 characteristics were not significant. Age, sex, obesity, diabetes, hypertension, a history of obstructive pulmonary disease and unstable angina were not predictive of the duration of intensive care stay. Multivariate analysis indicated that only left ventricular end diastolic pressure and the number of diseased coronary arteries predicted fast track patients. These criteria separated patients into three groups. Those who were good risk had one or two vessel disease and left ventricular end diastolic pressure < 13 mm Hg. They comprised 19% of the total and 93% of them were fast track. Those who were intermediate risk had either three vessel disease or left ventricular end diastolic pressure > 13 mm Hg but not both. They comprised 49% of the total and 85% of them were fast track. Those who were poor risk had both three vessel disease and left ventricular end diastolic pressure > 13 mm Hg. They comprised 32% of the total and 62% of them were fast track. The 106 (24%) patients who spent < or = 7 days in hospital after surgery were significantly younger (mean (SD) 55(8) v 58(8) years; P < 0.001) with a lower incidence of previous myocardial infarction (positive predictive accuracy 30%, sensitivity 53%), were less likely to have a history of obstructive pulmonary disease (25%, 98%), and more likely to have one or two vessel coronary disease (33%, 41%). They were more likely to have an internal mammary artery as a bypass conduit (27%, 89%) and more likely to need fewer than three distal anastomoses of the vein graft (29%, 63%). By multivariate analysis only age was significantly predictive of hospital stay. Total hospital stay could not be satisfactorily modelled on the basis of the criteria tested here. Sex, obesity, diabetes, hypertension, unstable angina, renal function, and left ventricular function were not associated with hospital stay. CONCLUSIONS-Most patients who had coronary artery surgery spent less than or equal to 24 hours in intensive care, but most spent > 7 days in hospital. The chance of a patient spending less than or equal to 24 hours in intensive care could be predicted by the number of coronary arteries diseased and the left ventricular end diastolic pressure. Poor risks patients (32%) had only a 62% chance of an intensive care unit stay of less than or equal to 24 hours. A policy of scheduling no more than one such patient for surgery per day would be simple to institute and would maximise the use of surgical capacity.